2011
DOI: 10.1161/strokeaha.110.596650
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Tensor MRI Reveals Chronic Alterations in White Matter Despite the Absence of a Visible Ischemic Lesion on Conventional MRI

Abstract: Background and Purpose-The impact of stroke on white matter is poorly described in preclinical investigations mainly based on rodents with a low white (WM)/gray matter ratio. Using diffusion tensor imaging, we evaluated WM alterations and correlated them with sensorimotor deficits after stroke in the marmoset, a nonhuman primate that displays a WM/gray matter ratio close to that of humans. Methods-Marmosets underwent a transient brain ischemia (3-hour). Eight serial MRI examinations were made during ischemia a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 19 publications
3
17
1
Order By: Relevance
“…In addition, the inter-voxel metric measuring the standard deviation of the angle of the first eigenvector projection within a neighborhood revealed WM abnormalities in the chronic phases of ischemia. In this study, the FA/MD metrics failed to uncover any WM differences [20]. Together, these reports and the current study suggest that the inter-voxel indices (e.g., LDH) may be applied when no significant results are found by assessing FA/MD.…”
Section: Discussionsupporting
confidence: 40%
See 1 more Smart Citation
“…In addition, the inter-voxel metric measuring the standard deviation of the angle of the first eigenvector projection within a neighborhood revealed WM abnormalities in the chronic phases of ischemia. In this study, the FA/MD metrics failed to uncover any WM differences [20]. Together, these reports and the current study suggest that the inter-voxel indices (e.g., LDH) may be applied when no significant results are found by assessing FA/MD.…”
Section: Discussionsupporting
confidence: 40%
“…In addition, a recent nonhuman primate study applied another inter-voxel index that measures the standard deviation of the angle of the first eigenvector projection within a neighborhood. This study demonstrated WM abnormalities during the chronic stage of induced cerebral ischemia [20]. Intriguingly, the studies that have applied both inter- and intra-voxel indices (e.g., FA and MD) have shown discrepant results between the indices.…”
Section: Introductionmentioning
confidence: 57%
“…Only a few intervoxel measures have been developed, [14,15] and all are based on the diffusion tensor model. Hence, these studies are all limited by the problematic assumption that a simple Gaussian profile can be applied to water diffusion in complex anatomical structures.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, marmoset models have been developed for dengue virus infection [7], smallpox [8], and Karposi's sarcoma [9]. In neuroscience research, marmoset models have been developed recently for the study of temporal lobe epilepsy [10] as well as stroke and ischemia [11]. These join the more established models of Parkinson's disease [12], Huntington's disease [13], Alzheimer's disease [14] and multiple sclerosis [15].…”
Section: Introductionmentioning
confidence: 99%